2009
DOI: 10.1103/physrevb.79.094517
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of resonant and transient phenomena in Josephson junction flux qubits

Abstract: We present an analytical and computational study of resonances and transient responses in a classical Josephson junction system. A theoretical basis for resonances in a superconducting loop with three junctions is presented, outlining both the direct relationship between the dynamics of single-and multijunction systems and the direct relationships between observations of the classical counterparts to Rabi oscillations, Ramsey fringes, and spin-echo oscillations in this class of systems. We show simulation data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…However, it was soon demonstrated that even these features could be explained as consequences of the RCSJ model of Josephson systems. Both Ramsey fringes [55] and spin echo oscillations were reproduced for a single junction system [56] and for SQUIDs [57]. Ramsey fringes and spin echo-like effects could be activated in Josephson junction systems by appropriate combined sequences of pumping and probe pulses.…”
Section: B Ramsey Fringes and Spin Echoesmentioning
confidence: 91%
See 2 more Smart Citations
“…However, it was soon demonstrated that even these features could be explained as consequences of the RCSJ model of Josephson systems. Both Ramsey fringes [55] and spin echo oscillations were reproduced for a single junction system [56] and for SQUIDs [57]. Ramsey fringes and spin echo-like effects could be activated in Josephson junction systems by appropriate combined sequences of pumping and probe pulses.…”
Section: B Ramsey Fringes and Spin Echoesmentioning
confidence: 91%
“…38 (Fig 4 from [52]) we show Rabi oscillations and Ramsey fringes measured on a SQUID system investigated from the "quantum" point of view, (Fig. 5 from [57]) we show results of RCSJ simulations of the same system. As can be seen in these cases, like in all the others already discussed, the agreement of the RCSJ output with the experiments is remarkable.…”
Section: B Ramsey Fringes and Spin Echoesmentioning
confidence: 95%
See 1 more Smart Citation
“…The quantum-mechanical versus a (semi)classical description of the qubit-EM field coupled systems still has certain controversies [42]. Nevertheless, at low temperatures, a fully quantum treatment is justified, while the dissipation is negligible.…”
Section: Quantization and Two-level Approximationmentioning
confidence: 99%
“…The resulting symmetric and anti-symmetric superposition states form the ground and excited states of the flux qubit separated by the minimal energy splittingh . Note that our terminology follows the most popular approach based on macroscopic quantum tunneling [21]; however, interpretations based on the resistively and capacitively shunted junction model [34][35][36] have not been ruled out yet. In the basis of the persistent current states and near the symmetry point, the Hamiltonian describing the flux qubit can be written as [26]…”
Section: The Fixed-gap Flux Qubitmentioning
confidence: 99%